2015
DOI: 10.1089/scd.2015.0070
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Adhesion-Related Proteins and MAPK Pathways Lead to Suitable Osteoblast Differentiation of Human Mesenchymal Stem Cells Subpopulations

Abstract: Cellular adhesion enables communication between cells and their environment. Adhesion can be achieved throughout focal adhesions and its components influence osteoblast differentiation of human mesenchymal stem cells (hMSCs). Because cell adhesion and osteoblast differentiation are closely related, this article aimed to analyze the expression profiles of adhesion-related proteins during osteoblastic differentiation of two hMSCs subpopulations (CD105(+) and CD105(-)) and propose a strategy for assembling bone g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Indeed, CD105 high MSCs were shown to differentiate more effectively into chondrocytes compared to CD105 low MSCs [28]. Moreover, hMSCs expressing low CD105 exhibited increased osteogenic gene expression and were more prone to osteogenic differentiation [6,29]. In agreement with these studies, the present study revealed that CD105 low population of hMSCs induced by long-term MC-A-treatment exhibited reduced chondrogenic differentiation potential.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, CD105 high MSCs were shown to differentiate more effectively into chondrocytes compared to CD105 low MSCs [28]. Moreover, hMSCs expressing low CD105 exhibited increased osteogenic gene expression and were more prone to osteogenic differentiation [6,29]. In agreement with these studies, the present study revealed that CD105 low population of hMSCs induced by long-term MC-A-treatment exhibited reduced chondrogenic differentiation potential.…”
Section: Discussionsupporting
confidence: 88%
“…However, it has been noted that CD105 + MSCs have no superior chondrogenic potential than the CD105ones [68], even though it is still controversial [69]. It has also been stated that, as a counterpart of decreased chondrogenic potential, CD105 -MSCs show increased osteogenic potential [69] as a result of superior adhesion and mineralization efficiency [70], which might be related to the superior osteogenic potential of iMSCs. Nevertheless, surface marker expression does not necessarily reflect the functional capacities of MSC [63], and the inferior osteogenic potential of primary MSC#6 may be also due to them being differentiated at the 6th passage, when cells are expected to be aged [5,71].…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Furthermore, through in vivo trials, it was demonstrated that grafts containing CD105- cells promoted adequate graft integration, improved host vascular infiltration, and facilitated efficient repair through intramembranous ossification. By contrast, grafts containing CD105+ cells showed abundant fibrocartilaginous tissue and deficient endochondral ossification [ 67 ].…”
Section: Advances In Related Basic Researchmentioning
confidence: 99%